Volume 1: Aerospace Engineering Division Joint Track; Computational Fluid Dynamics 2021
DOI: 10.1115/fedsm2021-60958
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study on Wing-Lambda-Shock Formation

Abstract: It is well-known that a wing is one of the most important parts of an aircraft as it is used to generate lift force. According to a wing moving at sufficiently high subsonic speeds, the flow speed on the wing’s upper surface can be supersonic due to acceleration through the curvature-created suction, thereby forming a shock wave in a lambda shape. Additionally, the lambda shock can interact with the boundary layer flow. These phenomena relate to disturbances in the flow field, including flow separation, thus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…At a high subsonic speed, a noteworthy occurrence takes place on the upper surface of the unfolded wing, wherein localized supersonic regions emerge, leading to the formation of a λ-shock [24,25], as depicted in Figure 9a. Simultaneously, under the current freestream conditions and angle of attack, it is observed that the wingtip vortices and vortices resulting from flow separation on the upper surface of the wing exhibit a tendency to coalesce.…”
Section: The Steady Aerodynamic Characteristics Of Folding Wingmentioning
confidence: 99%
“…At a high subsonic speed, a noteworthy occurrence takes place on the upper surface of the unfolded wing, wherein localized supersonic regions emerge, leading to the formation of a λ-shock [24,25], as depicted in Figure 9a. Simultaneously, under the current freestream conditions and angle of attack, it is observed that the wingtip vortices and vortices resulting from flow separation on the upper surface of the wing exhibit a tendency to coalesce.…”
Section: The Steady Aerodynamic Characteristics Of Folding Wingmentioning
confidence: 99%